RADIOMETRIC STUDY OF RADIONUCLIDES IN WATER AROUND THE ARNASAY-AYDARKOL REGION - Jonzoqov, Azizjon; Bo'riboyeva, Vazira (Физико-технологического образование, 2021)
In the article a comprehensive assessment of the radiation safety of natural and underground water is studied. The radiometric analysis were used to determine the radiation contamination of water with natural radionuclides